Foreign body in the appendix presenting as acute appendicitis: a case report. (December 2016) - Sama, Carlson; Aminde, Leopold; Njim, Tsi; Angwafo, Fru
Abstract Background Foreign bodies are a rare cause of appendicitis. In most instances, ingested foreign bodies pass through the alimentary tract asymptomatically. However, those that enter the lumen of the vermiform appendix may not be able to re-enter the colon and may initiate an inflammatory process. We report a case of acute appendicitis induced by an unusual foreign body. Case presentation A 26-year-old Sub-Saharan woman presented with right iliac fossa pain and tenderness. She underwent an open appendectomy which revealed a condom fragment within the appendiceal lumen. A detailed retrospective history confirmed accidental ingestion of the condom 2 weeks prior to onset of symptoms. Conclusions Although a rare finding, a variety of foreign bodies can be lodged in the appendix and may instigate an inflammatory process. There is a need to increase awareness of the potential dangers of ingested foreign bodies.